Multidirectional model to generate educational innovation - Urcid Puga, Rodrigo (2018)
This article aims to present a model that reflects the need for educational innovation that higher education institutions (HEIs) should consider when restructuring their administration, renewing their educational curriculum including entrant/graduate profiles, and collaborating with the various interest groups within the industry and society. The methodology of this study is qualitative, supported by a documented and cross-sectional investigation. As a result, a model is shown that represents the various elements that make up the need and relevance of educational innovation in HEIs. Through this model, educational innovation is shown to be a current necessity and all HEIs must assume their capacities to give it importance and take action for change.